O Brasil de desenho : uma análise de personagens brasileiros nas animações de Hollywood - Rocha, Anderson Alves da (2014)
This work has as main purpose investigating the relationship between American film production, especially related to the animated film, with the portrayal of characters and typically Brazilian scenarios in the films "Watercolor of Brazil" of 1943 and "Rio" of 2011. To that effect, the literature review research directed to the understanding of cinema as a creative agent of realities, traditions and symbols, which now spread through the mass media. In film analysis, the aim is to determine which the main points approximation and distancing between the two works, from an aesthetic and cinematic view. To do so, remarkable features of the production of Hollywood during the relative period the works are presented, the Golden Age and the New Hollywood, respectively. The paper proposes also discuss the mechanisms of identities creation, based on the mass communication, especially with the support from the Cultural Studies. The research also provides a description of the two works analyzed, such as the detailed transcript of animations, technical and conceptual information about the production as well as the history and impact of the movies. Through the analysis, it can be seen that the films have had a prominent role in the distribution of information and the characterization of Brazil in the imagination of the public inside and outside the country through the mass communication. From cinematographic point of view, is visible the clear relationship between the two works, on the colors, soundtracks and scenes.